REQUIREMENTS OF THE INFORMATION SOCIETY OF THE REPUBLIC OF KAZAKHSTAN TO THE LEVEL OF IT-SPECIALISTS TRAINING - Yelena A. Spirina (Открытое образование (Москва))
The article analizes the concept of “Information society”. The author describes normative documents regulating the formation of the information society in the Republic of Kazakhstan. The main tasks and requirements for IT-specialists are highlighted in the abstract. We analyze the content of the training students of the information specialties to perform tasks of the Information Society of the Republic of Kazakhstan.